Control interno en la administración de propiedad planta y equipo del Cuerpo de Bomberos del Cantón Vinces - Santana Correa, Aylí Jazmín (2020)
An internal control manual establishes the methodology that an institution, whether public or private, must follow for the correct management and operation of its fixed assets of a company. Particles have been taken as a case of the Vinces Canton Fire Department, whose investigation is focused on the improvement and control of Property, Plant and Equipment in the Vinces Canton Fire Department, through which it was possible to determine some shortcomings regarding to the factors associated to have a better internal control in your Property, Plant and Equipment and its corresponding valuation over time. For this purpose, an interview questionnaire is developed that will be applied to the personnel of the warehouse department that is part of the Bomberil institution, resulting in a weak level of confidence and risk of control, lack of a defined and approved system for the correct control and administration of Property, Plant and Equipment, existing errors in accounting records and non-compliance with the Administration Manual and Control of Public Sector Assets, which must be governed. Hence the great importance of applying the associated factors in order to improve the control of property, plant and equipment, because it is the best strategy to achieve excellence in the institution's performance, given the importance it has in the community, for the support it provides when a disaster or any type of accident occurs that affects the members of said community.